2023
DOI: 10.1007/s11357-023-00744-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating instruments for assessing healthspan: a multi-center cross-sectional study on health-related quality of life (HRQL) and frailty in the companion dog

Abstract: Developing valid tools that assess key determinants of canine healthspan such as frailty and health-related quality of life (HRQL) is essential to characterizing and understanding aging in dogs. Additionally, because the companion dog is an excellent translational model for humans, such tools can be applied to evaluate gerotherapeutics and investigate mechanisms underlying longevity in both dogs and humans. In this multi-center, cross-sectional study, we investigated the use of a clinical questionnaire (Canine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In other words, dogs weighing over 30 kg may be the most strongly affected by an early-onset physical decline (as suggested in [ 18 ]), and this physical decline and accumulating health problems are the main cause of their age-related behavioral changes, which occur before significant cognitive (neural) decline begins. This hypothesis is indirectly supported by the result of Chen et al [ 59 ] that larger dogs showed faster age-related decline in health-related quality of life scores (especially in activity and comfort) than smaller dogs. Nevertheless, further studies are needed to find direct support for it.…”
Section: Discussionmentioning
confidence: 72%
“…In other words, dogs weighing over 30 kg may be the most strongly affected by an early-onset physical decline (as suggested in [ 18 ]), and this physical decline and accumulating health problems are the main cause of their age-related behavioral changes, which occur before significant cognitive (neural) decline begins. This hypothesis is indirectly supported by the result of Chen et al [ 59 ] that larger dogs showed faster age-related decline in health-related quality of life scores (especially in activity and comfort) than smaller dogs. Nevertheless, further studies are needed to find direct support for it.…”
Section: Discussionmentioning
confidence: 72%